Impact of provitamin A biofortified maize consumption on carotenoid status of Zambian children - Craft, Neal E.; Palmer, Amanda; Schultze, Kerry; Chileshe, Justin; Barffour, Maxwell; Siamusantu, Ward; Klemm, Rolf; West, Keith (Wiley, 2017)
Objectives Provitamin A carotenoid biofortified “orange” maize has been developed as a vitamin A deficiency control strategy using selective breeding for the β-carotene hydroxylase-1 gene, which increases β-carotene, β-cryptoxanthin, and zeaxanthin in the endosperm. We conducted a cluster-randomized trial to test the impact of orange maize consumption (a predominantly β-carotene-rich variety) on serum retinol concentration in rural Zambian children (4–8 y). In the present analysis, we tested the intervention’s impact on circulating carotenoids. Methods Children (n=1024, 4–8 y) were cluster-randomized to receive 200 g dry weight/d orange or conventional “white” maize prepared with standardized low-vitamin A relishes, 6 d/w for 6 m. The carotenoid profile was assessed in baseline and follow-up serum samples in a subset (n=321 white, n=358 orange) of children. We assessed differences in log-transformed carotenoids, expressed as geometric means and 95% confidence limits, accounting for cluster randomization. Results Baseline carotenoids did not differ between groups. There were no differences in lycopene and lutein between groups at follow-up. Other carotenoids increased significantly (p<0.001) in orange vs white groups following the six-month intervention: β-carotene [273 (254,292) vs 147 (135,160) nmol/L], α-carotene [19.7 (18.4,21.1) vs 10.6 (9.9,11.3) nmol/L], β-cryptoxanthin [36.1 (33.6,38.8) vs 12.6 (11.8,13.5) nmol/L], α-cryptoxanthin [18.7 (17.4,20.1) vs 8.9 (8.4,9.4) nmol/L], zeaxanthin [127 (119,135) vs 81 (75,88) nmol/L]. Conclusions Children regularly consuming a biofortified maize variety bred primarily for β-carotene had higher concentrations of other provitamin A carotenoids and zeaxanthin, suggesting the potential for health benefits beyond vitamin A deficiency control.